Babyblues Syndrome dalam Al-Quran: Analisis Kontekstual Surat Maryam Ayat 21-30 - Fadlilah, Annisa; Christiani, Putri Margareta Lucky (Program Pascasarjana UNU Surakarta, 2025)
Baby blues, also known as postpartum blues, is a temporary mood disorder that can affect new mothers. This syndrome experienced by these women can occur due to many factors, internal and external. This research looks at the phenomenon of Baby blues syndrome experienced by Maryam in Surah Maryam 21-30. The method applied in this research is the thematic method for certain letters using Abdullah Saeed's Contextual Tafsir theory. The research sources are the Al-Qur'an and Tafsir Books, in this case, the research object is Surah Maryam verses 21-30. The results of the research are: identification of the world of the text shows that Maryam's letter fell into patriarchal social conditions; the structure of the text in this letter coherently describes the process of Maryam's pregnancy until she gave birth to Isa amidst the ridicule of the children of Israel; Recipients of revelation viewed the text during the time of the prophet Muhammad who already knew Isa with a different concept; The contextual interpretation of Maryam's letter 21-30 is the phenomenon of Baby blues syndrome experienced by Maryam; Maryam's support system in giving birth to Isa as prevention of baby blues; Nutrition for pregnant women, and external pressure and how to overcome it as an effort to avoid baby blues syndrome.